Por outro chão na formação docente contemporânea - Nunes, Karen Raíssa (2022)
This study emerges from the researcher's need to explain her discomforts in the face of the teaching training environment, which were historically constituted starting in childhood until arriving at the Professional Master's in Education: Teacher Training, where she encountered discussions in defense of the ground. from school. In line with her interests, within the master's degree comes the invitation to investigate a new universe: it was the study of the Klauss Vianna Technique (TKV). In an articulated way with the study of TKV, we also get in touch with the references of the Critical Theory of Society, through philosophical concepts, which expand the understanding of the artifices used by neoliberal society and the objectified form that the technique has assumed in recent times. current. Thinking in this way, the thesis is built throughout this research that, in contemporary times, teacher training is also objectified, modeling itself to the generalized spirit of the commodity, where technique is taken as its own end and the human being as a means. . This tendency is investigated by the philosopher Theodor W. Adorno in culture as semi-formation (2010). Thus, based on the Adornian thought of semitraining for the educational field - pointed out more specifically in this research within the Professional Master's in Education -, this means that there is an exaggerated emphasis on technique, from which it is verified and required the maddened production of scientific materials, and also the direction to carry out "refreshing courses", in addition to the excess of stimuli that individuals end up undergoing through the relationship with different technological devices - aggravated in remote teaching by the pandemic situation - altering if subjectivity. As a manifestation of semi-formative processes, this corroborates sensory desensitization. With all this on the horizon, in order to inspire the teaching training environment, this work seeks to recover a sense of technique (kept alive today by the tradition of the Vianna School, thanks to its disseminators), conceived at the intersection of the territories of Theater and Dance. and opened based on the investigations of dancer, choreographer and body coach Klauss Vianna. In this way, the research undertaken here through the experimentation of TKV in the body of the researcher-teacher and through the narration, emphasizes that the body and its expressiveness are not mere materials to operationalize a technique, nor a model of education, but the technique , when apprehended as something of a procedural nature, it is rather a means to potentiate bodily movements, the recognition of their senses, imaginative and reflective capacities, understandings that are dear to the training of teachers as Bildung.